2023
DOI: 10.3390/cancers15102708
|View full text |Cite
|
Sign up to set email alerts
|

[89Zr]-Atezolizumab-PET Imaging Reveals Longitudinal Alterations in PDL1 during Therapy in TNBC Preclinical Models

Abstract: Triple-negative breast cancers (TNBCs) currently have limited treatment options; however, PD-L1 is an indicator of susceptibility to immunotherapy. Currently, assessment of PD-L1 is limited to biopsy samples. These limitations may be overcome with molecular imaging. In this work, we describe chemistry development and optimization, in vitro, in vivo, and dosimetry of [89Zr]-Atezolizumab for PD-L1 imaging. Atezolizumab was conjugated to DFO and radiolabeled with 89Zr. Tumor uptake and heterogeneity in TNBC xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The nontarget uptake can be attributed to PD-L1 expression in some normal organs and the elimination of mAbs in vivo. Notably, the results of biodistribution in this study are similar to those of other studies examining the uptake of 89 Zr-DFO-anti-PD-L1-mAb tracers in nontarget organs rich in PD-L1, such as the heart, spleen, lymph nodes, intestines, pancreas, and skin [67,68]. However, the effects of tracer accumulation in normal organs on the imaging of PD-L1 expression in tumors remain unclear and require further investigation.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The nontarget uptake can be attributed to PD-L1 expression in some normal organs and the elimination of mAbs in vivo. Notably, the results of biodistribution in this study are similar to those of other studies examining the uptake of 89 Zr-DFO-anti-PD-L1-mAb tracers in nontarget organs rich in PD-L1, such as the heart, spleen, lymph nodes, intestines, pancreas, and skin [67,68]. However, the effects of tracer accumulation in normal organs on the imaging of PD-L1 expression in tumors remain unclear and require further investigation.…”
Section: Discussionsupporting
confidence: 82%
“…These findings suggest that tracer_20X, with its relatively high specific activity (10.5 ± 1.6 µCi/µg), can enhance the tumor imaging ability compared with that of the traditional tracer_3X with a relatively low CAR (2.2 ± 0.6 µCi/µg). Many studies have reported that blocking experiments involving the coinjection or preinjection of unlabeled anti-PD-L1-mAb in excess (3-100-folds) with the tracer protein during 89 Zr-iPET scans may enhance tumor imaging characteristics and reduce tracer uptake in PD-L1-expressing nontarget organs and tissues, such as the spleen and lymph nodes [49,56,62,63,67,68]. However, even in the absence of blocking experiments during 89 Zr-iPET imaging in this study, clear tumor images were observed in different tracer groups.…”
Section: Discussionmentioning
confidence: 99%
“…The respective tumor volume was calculated according to the following equation: tumor volume (mm 3 ) = d 2 × D/2 (where d is the shortest diameter and D the longest diameter). The animals were subjected to μPET imaging, when tumors reached a volume of at least 200 mm 3 . Tumor volume never exceeded 1 cm 3 .…”
Section: Notesmentioning
confidence: 99%
“…However, the clinical success of PD-L1 checkpoint therapy has unveiled complex challenges, including response heterogeneity, resistance, and the need for accurate patient stratification. In this context, positron emission tomography (PET) radiotracers, particularly radiolabeled antibodies, have emerged as promising tools to address these challenges by enabling longitudinal, noninvasive, real-time assessment of PD-L1 expression and immune response dynamics. , One of the most promising applications of PD-L1 PET radiotracers is patient stratification. By identifying patients with high PD-L1 expression and an active antitumor immune response, PET imaging can guide the selection of individuals who are most likely to respond to PD-L1 checkpoint inhibitor therapy .…”
Section: Introductionmentioning
confidence: 99%
“…6,10,11 It seems that molecular imaging is more suitable than invasive biopsy in the diagnosis and stages of cancers. Antibody-based probes, such as [ 89 Zr]Zr-atezolizumab 12 and [ 64 Cu]Cu-DOTA-HAC-PD1, 13 have presented the feasibility of imaging PD-L1 in the clinic. However, these antibody-based radiotracers are subject to the disadvantages of expensive costs, limited penetration and immunogenicity.…”
Section: Introductionmentioning
confidence: 99%